PENANAMAN NILAI PENDIDIKAN KARAKTER MELALUI CERITA RAMAYANA PADA PEMBELAJARAN PENDIDIKAN AGAMA HINDU DAN BUDI PEKERTI DI SD FAJAR HARAPAN - I Putu Suyasa Ariputra (Jurnal Penjaminan Mutu, 2024)
This study seeks to examine the process of instilling character education values through the Ramayana story in the context of Hindu Religious Education at SD Fajar Harapan. The Ramayana, a narrative rich in life values such as hard work, responsibility, social care, and creativity, serves as a key educational tool for fostering character development in students. Employing a descriptive qualitative approach, this research gathers data through observations, interviews, and document analysis. The results indicate that teachers play a pivotal role in guiding students to identify and comprehend the character values embedded in the Ramayana. Through the use of video-based learning strategies, students are encouraged to observe and analyze the characters within the story, followed by group discussions that facilitate the differentiation between positive and negative values. The internalization of these values occurs progressively, beginning with the teacher's interpretation and transitioning into interactive discussions that allow students to relate these values to their everyday lives. In conclusion, the Ramayana story proves to be an effective medium for character education, particularly within an educational framework that prioritizes cultural and local value approaches.